2022
DOI: 10.3390/mti6010004
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Musical Interactions

Abstract: The article presents a contextual survey of eight contributions in the special issue Musical Interactions (Volume I) in Multimodal Technologies and Interaction. The presentation includes (1) a critical examination of what it means to be musical, to devise the concept of music proper to MTI as well as multicultural proximity, and (2) a conceptual framework for instrumentation, design, and assessment of musical interaction research through five enabling dimensions: Affordance; Design Alignment; Adaptive Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Similarly, non-destructive processing enables feedback recipients to easily compare pre-/post-feedback artefact states, a practice which over time can enhance the practitioners' perceptual skills [33,34]. When examined in the specific context of musical artefacts, our design aligns well with three of the five enabling dimensions to consider for musical interaction as suggested by Chao [3] and these are affordance, design alignment and temporal integration.…”
Section: Design Rationalementioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, non-destructive processing enables feedback recipients to easily compare pre-/post-feedback artefact states, a practice which over time can enhance the practitioners' perceptual skills [33,34]. When examined in the specific context of musical artefacts, our design aligns well with three of the five enabling dimensions to consider for musical interaction as suggested by Chao [3] and these are affordance, design alignment and temporal integration.…”
Section: Design Rationalementioning
confidence: 91%
“…We conclude this paper by discussing insights from this pilot study, focusing on observed issues around clarity, level of detail, control and artistic vision. Through this work, we also aim to make a contribution to the community's understanding of how the interactions with multimodal feedback impact music learning, part of the bigger question around interaction with multimodal technologies and perceptual processing and musical experiences as asked by Chao [3] in MITi's especial issue on 'Musical Interactions' in 2022.…”
Section: Introductionmentioning
confidence: 99%